Generation of an induced pluripotent stem cell line (DHMCi007-A) from a patient with autosomal recessive polycystic kidney disease (ARPKD) carrying a homozygous missense mutation in the fibrocystin-encoding PKHD1 gene - Tabatabaeifar, Mansoureh; Fluhr, Theresa; Syring, Hanna; Göhring, Gudrun; Schaefer, Franz; Jung-Klawitter, Sabine (Stem cell research, 2021)
Autosomal recessive polycystic kidney disease (ARPKD) is a severe pediatric kidney disorder primarily caused by mutations in the fibrocystin-encoding PKHD1 gene. It is characterized by the progressive development of cysts, eventually leading to renal failure. In order to create patient specific iPSCs, peripheral blood mononuclear cells (PBMCs) from a female patient carrying a homozygous PKHD1 mutation (c.8285A>T(;)(8285A>T)) were reprogrammed using the non-integral Cytotune®-iPS 2.0 Sendai Reprogramming Kit (Invitrogen). Morphology and karyotype of the cells are normal. Pluripotency hallmarks as well as the potential to spontaneously differentiate into all three germ layers were shown by immunofluorescence staining and RT-PCR.